Economic feasibility of irrigation under conditions of risk, in the subtropical climate regions. I. Maize crops - Franke, Alberto Elvino; Dorfman, Raul (Pesquisa Agropecuaria Brasileira, 1998)
This study was performed to estimate the economic feasibility, under conditions of risk, when spray irrigation is used on maize crops (Zea mays L.) in the subtropical climate regions. A series of 10 years of daily meteorological data from the meteorological stations of Cruz Alta and Passo Fundo, both in Rio Grande do Sul State was used to simulate irrigation needs using a water balance model. Needs were simulated for mutual combination of sites (agriecological regions of Missões and Planalto Médio); sowing seasons (Sep. 1st, Sep. 15th, Oct. 1st, Oct. 15th, Nov. 1st, Nov. 15th, Dec. 1st, Dec. 15th); irrigation management levels (for 100, 90, 80, 70 and 60 % of the potential crop yield) and levels of risk (2, 5, 10, 15, 20, 25, 30, 35 and 40%). The results indicate that irrigation, in maize, is economically feasible over broad range of combinations of the variables analized.